2021
DOI: 10.1186/s12876-021-01793-7
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of OLL1073R-1 yogurt improves psychological quality of life in women healthcare workers: secondary analysis of a randomized controlled trial

Abstract: Background We conducted a randomized controlled trial to investigate the effects of consumption of yogurt fermented with Lactobacillus delbrueckii ssp. bulgaricus OLL1073R-1 in women healthcare workers. In a previous study we used these data to investigate hypothesized preventive effects against flu, however any effects on improving mental quality of life were not analyzed at that time. In the present study, we focus on that aspect. Methods The par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Some were subjective (e.g., self-reported health and sleep quality), and others were objective (e.g., inflammatory markers and stress hormones). Certain subjective outcomes such as mood 42,47 self-rated health, 44,47 and sleep quality 46,47 improved in probiotics groups, whereas others such as anxiety and depression did not differ between the probiotic and control groups. Additionally, there were no significant differences reported for the majority of inflammatory markers and stress hormones measured between treatment groups, whereas absenteeism and presentism were found to be consistently reduced in the probiotic groups, but not in the control groups.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Some were subjective (e.g., self-reported health and sleep quality), and others were objective (e.g., inflammatory markers and stress hormones). Certain subjective outcomes such as mood 42,47 self-rated health, 44,47 and sleep quality 46,47 improved in probiotics groups, whereas others such as anxiety and depression did not differ between the probiotic and control groups. Additionally, there were no significant differences reported for the majority of inflammatory markers and stress hormones measured between treatment groups, whereas absenteeism and presentism were found to be consistently reduced in the probiotic groups, but not in the control groups.…”
Section: Discussionmentioning
confidence: 90%
“…Of these 24 studies, nine were excluded because the probiotic intervention was not delivered orally and three were excluded because they were not clinical trials. Two additional studies were identified when reviewing reference lists during the full‐text review process, resulting in 14 papers in the review 34–47 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations